Ordinaires, dégradés ou patrimoniaux ? - Aziz Ballouche (Projets de Paysage)
The savannah is an ordinary landscape found in rural areas of Sudano-Sahelian West Africa resulting from the continuous interaction between indigenous agro-pastoral societies and their environment. This article examines the long history of these interactions to identify the legacies in the current landscapes and to trace their past. This knowledge is then used to conduct a critical study of treatises on the anthropization of the savannah and their consequences in terms of heritagisation.